2014
DOI: 10.1097/hjh.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin ameliorates cardiac fibrosis and improves left ventricular diastolic function in hypertensive diastolic heart failure model rats

Abstract: Atorvastatin administration ameliorates cardiac fibrosis and improves left ventricular diastolic function in Dahl salt-sensitive rats. Lowering HSP47 by atorvastatin via inhibition of Rho-Rho kinase pathway is suggested as a mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In addition, HSP47 has been found to be associated with fibrosis level after myocardial infarction (43). Another study suggested that the beneficial effect of atorvastatin on cardiac fibrosis may be due to lowered HSP47 levels (34). The results of the present study are consistent with the aforementioned studies, with statins having the strongest effect among the tested drugs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, HSP47 has been found to be associated with fibrosis level after myocardial infarction (43). Another study suggested that the beneficial effect of atorvastatin on cardiac fibrosis may be due to lowered HSP47 levels (34). The results of the present study are consistent with the aforementioned studies, with statins having the strongest effect among the tested drugs.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of these effects may be related to suppression of the MVA pathway and downstream GTPase activity (30,31). Some cell culture and animal studies have suggested that statins can prevent the development of cardiac hypertrophy and fibrosis (32)(33)(34)(35), which may reduce ventricular compliance and is a major cause of cardiac diastolic dysfunction (36). A meta-analysis of 11 eligible studies, including 17,985 patients with heart failure with a preserved ejection fraction demonstrated that statin therapy may be associated with improved survival rates in these patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone may have an adverse effect on cardiac and vascular fibrosis 24 34. Although statins have been shown to decrease myocardial fibrosis in several animal models,9 10 clinical evidence is rare. One study showed that statins decrease circulating fibrosis markers in patients with HF 12.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, atorvastatin appeared to directly inhibit collagen production by cardiac fibroblasts in a human cardiac fibroblast cell culture 7. In animal studies, statins have been found to improve postmyocardial infarction myocardial fibrosis,8 and to ameliorate cardiac fibrosis and improve diastolic function in a rat model with diastolic HF 9. In double-knockout mice with metabolic syndrome, rosuvastatin was also shown to decrease myocardial fibrosis 10.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, it has been hypothesized that the action of statins to reduce the accumulation and inflammation of epicardial adipose tissue might not only have a salutary effect on nearby coronary vessels, but also on the underlying ventricular myocardium. Such an action could explain why, in experimental models, statins ameliorate microcirculatory derangements, cardiac fibrosis and their associated echocardiographic ventricular filling abnormalities . As a result of these effects, the anti‐inflammatory action of statins might be useful (particularly in people with metabolic disorder) by acting primarily to prevent the development of HFpEF, rather than heart failure with a reduced ejection fraction (HFrEF) .…”
Section: Differential Effects Of Statins In Preserved Vs Reduced Ejementioning
confidence: 99%